Drug Use Evaluation of Beta-Blockers in Medical Wards of Nedjo General Hospital, Western Ethiopia. (1st June 2020) - Fekadu, Ginenus; Bekele, Firomsa; Bekele, Kumera; Hanbisa, Sagni; Belay, Gemechis; Maqbool, Mudasir
Abstract : Introduction . Beta-blocker use evaluation is a performance method that focuses on the evaluation of beta-blocker use processes to achieve optimal patient outcomes. Several studies conducted in different hospitals revealed a high incidence of inappropriate prescription of beta-blockers among hospitalized patients. Therefore, it is important to identify inappropriate beta-blocker prescribing since they may increase the risk of hospitalizations. Despite this, there was no study conducted related to drug use evaluation of beta-blockers in Nedjo general hospital (NGH). Thus, this study was aimed at assessing the use evaluation of beta-blockers in medical wards of NGH. Methods . A retrospective cross-sectional study was conducted at medical wards of NGH from January 1, 2016, to December 31, 2017. Results . Out of the total of 149 medical record of patients that contains beta-blockers, 84 (56.37%) were males and about one-third (31.54%) of the patients ages were between 41 and 50 years. Propranolol was the most commonly prescribed beta-blocker (62.76%), and 94.56% of beta-blockers were prescribed with correct indication. There were about 51%, 46.31%, 64.43%, and 46.98% of beta-blockers prescribed with the correct dose, duration, frequency, and route of administration, respectively. Regarding the routes of administration, 70 (46.98%) of them were prescribed with the correct route. Most drugs interacting were propranolol with cimetidine 26 (68.42%), and the most frequent condition for which beta-blockers were prescribed was hypertension (32.89%). Conclusion . Overall, there was an inappropriate use of beta-blockers in terms of dosage and durations. So, prescribers of NGH should strictly adhere to the national treatment guideline when prescribing medications. Additionally, drug information centers have proved useful and effective in promoting rational drug use. Hence, it should be recommended for general use.